Counteracting the Neoliberal Carceral U.S. University: Academic Freedom through Decoloniality and Epistemology - Dell'Orso, A. (Academic Freedom and Silencing in Times of Genocide Workshop, 2025)
In an era tainted by genocide and ongoing colonial violence within the United States, Palestine, and beyond, U.S. academia operates within a neoliberal carceral framework that suppresses dissent and restricts academic freedom. How can epistemology and decoloniality counteract the carceral politics embedded in U.S. higher education institutions? The punitive, individualistic nature of the carceral culture of the U.S. settler colonial state undermines justice, transformation, and collective liberation. Within this system, academic repression, policing, and surveillance impede the autonomy and intellectuality of scholars, particularly those resisting epistemicide and advancing decolonial thought. The neoliberal university prioritizes compliance, shame, and institutional control, often under the guise of accountability, while disregarding any genuine processes of restoration and collaboration. This squashing of dissent not only limits the possibilities for critical scholarship but also reinforces a broader societal trend that privileges policing and punishment over transformative justice. By interrogating institutional epistemology and the structures that prolong this academic silencing, we may discover alternative frameworks that foster collaborative knowledge production grounded in the cultivation of truth and justice. Collectively we may imagine and strategize ways to resist carceral logics in academia and build decolonial epistemic spaces beyond both extractivism and silencing.